Impact of Fires on Key Biodiversity Areas (KBAs) and Priority Bird Species for Conservation in Bolivia - Oswaldo Maillard; Sebastian K. Herzog; Rodrigo W. Soria-Auza; Roberto Vides-Almonacid (Fire, 2022)
Key Biodiversity Areas (KBAs) are sites that contribute significantly to the protection of the planet’s biodiversity. In this study, we evaluated the annual burned areas and the intensity of the fires that affected Bolivia and its 58 KBAs (23.3 million ha) over the last 20 years (2001–2020). In particular, we analyzed the impact of wildfires on the distribution of Bolivian birds at the levels of overall species richness, endemic species and threatened species (Critically Endangered, Endangered, Vulnerable). We found that at the KBA level, the cumulative area of wildfires was 21.6 million ha, while the absolute area impacted was 5.6 million ha. The KBAs most affected by the wildfires are located in the departments of Beni and Santa Cruz; mainly in the KBAs Área Natural de Manejo Integrado San Matías, Oeste del río Mamoré, Este del río Mamoré, Noel Kempff Mercado and Área Natural de Manejo Integrado Otuquis. The wildfires impacted the distribution of 54 threatened species and 15 endemic species in the KBAs. Based on the results of this study, it is a priority to communicate to Bolivian government authorities the importance of KBAs as a strategy for the conservation of the country’s biodiversity and the threats resulting from anthropogenic fires.